Analysis of Factors Causing Decrease In Heating, Ventilation, and Air Conditioning (HVAC) Performance Using A Cause Effect Diagram (Fishbone Diagram) - Hardimam Arbi; Hery Irwan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Heating, Ventilation, and Air Conditioning (HVAC) system is a supporting facility that functions to regulate temperature, humidity, air circulation, and indoor air quality to ensure smooth production processes. A decline in HVAC system performance can increase energy consumption, extend downtime, and reduce overall operational effectiveness. This study aims to identify the factors causing the decline in HVAC performance using the Cause-and-Effect Diagram (Fishbone Diagram). The research was conducted on the Air Handling Unit (AHU) at PT XYZ Batam using maintenance and failure data collected from January to December 2025. The research methods included field observations, documentation, and analysis based on the 6M approach, consisting of Man, Machine, Method, Material, Measurement, and Environment. The results showed a total of 61 failure incidents, with the most dominant failure being dirty air filters accounting for 18 cases (29.51%), followed by dirty cooling coils with 12 cases (19.67%), and worn blower belts with 9 cases (14.75%). The Fishbone Diagram analysis indicated that the Machine and Method factors were the primary causes of HVAC performance degradation, mainly due to dirty filters, contaminated cooling coils, and ineffective preventive maintenance practices. The proposed improvements include routine component cleaning, scheduled preventive maintenance, regular calibration of measuring instruments, the use of standard compliant spare parts, and technical training for maintenance personnel. Implementing these recommendations is expected to improve HVAC system reliability, reduce failure frequency, enhance energy efficiency, and support sustainable industrial operations.